The impact of the endocrine disruptors on child health - Donjeta Bali; Francesca Scaltrito; Maria Teresa Grimaldi; Ida Giardino; Massimo Pettoello-Mantovani; Maria Pastore (Elsevier, 2023)
During recent years, Endocrine Disruptor chemicals (EDCs) have been the subject of particular attention because they are ubiquitous and able to cause adverse effect in humans, and particularly in children. Substances capable of interfering with the normal activity of the endocrine system can be of both man-made and natural origin. They often come into contact with the body through diet, water, air or skin. However, although the body is continuously exposed to their action, it is difficult to fully quantify the negative effects of these substances. Available data show that individuals most exposed to endocrine disruptors more frequently have cancers, reproductive, (ie: infertility, endometriosis, miscarriage.), metabolic (ie: diabetes) and/or immune disorders. Behavioral and developmental disorders are also observed in children exposed to Endocrine Disruptors. The presence of EDCs has been demonstrated during pregnancy in maternal blood, urine, and hair. At the placental level, EDCs can affect normal development and endocrine function and promote inflammatory reactions. The aim of this brief narrative review is to raise the attention of general pediatricians on the most prevalent multiple or interconnecting risks caused by EDCs to children's health by summarizing the existing knowledge on these toxic chemicals. Authors also report the effort made by the European Union to develop an effective Hazard Control Decision Support System which aim is to improve risk-based procedures able of detecting, monitoring and managing toxic substances in food chain.